2022
DOI: 10.1161/hypertensionaha.121.18128
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Plaques From Symptomatic Patients With Mild Stenosis Is Associated With Intraplaque Hemorrhage

Abstract: Carotid plaque vulnerability features beyond the degree of stenosis may play a key role in the pathogenesis and recurrence of ischemic cerebrovascular events. This study sought to compare intraplaque hemorrhage (IPH) as a marker of plaque vulnerability in symptomatic patients with mild (<50%), moderate (50%–69%), and severe (≥70%) carotid artery stenosis. We included patients who experienced ischemic cerebrovascular events with no other identifiable sources and underwent carotid endarterectomy for mild (n=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 70 publications
(109 reference statements)
0
12
0
Order By: Relevance
“…31 Of all MR imaging biomarkers of plaque vulnerability, IPH has been most strongly associated with ipsilateral ischemia in patients with ESUS, even in cases of minimal luminal stenosis. 9,21,[32][33][34][35][36] In fact, our group has demonstrated that patients with ESUS with ipsilateral IPH had an annual recurrence rate of 9.5% compared with 2.5% in patients without IPH. 9 Perhaps the most convincing evidence to date comes from the aforementioned PARISK study, in which patients with MR imaging evidence of IPH were at higher risk of developing recurrent ischemic events at 5-year follow-up.…”
Section: Mr Imagingmentioning
confidence: 78%
“…31 Of all MR imaging biomarkers of plaque vulnerability, IPH has been most strongly associated with ipsilateral ischemia in patients with ESUS, even in cases of minimal luminal stenosis. 9,21,[32][33][34][35][36] In fact, our group has demonstrated that patients with ESUS with ipsilateral IPH had an annual recurrence rate of 9.5% compared with 2.5% in patients without IPH. 9 Perhaps the most convincing evidence to date comes from the aforementioned PARISK study, in which patients with MR imaging evidence of IPH were at higher risk of developing recurrent ischemic events at 5-year follow-up.…”
Section: Mr Imagingmentioning
confidence: 78%
“…[19][20][21][22][23][24][25] There was a higher prevalence of intraplaque hemorrhage (IPH) in ipsilateral plaques 19,24,25 and in plaques with a lower degree of stenosis. 26 In particular, mildly stenotic carotid arteries in patients with ESUS had higher IPH compared with moderate and severe stenosis. 26 The pooled prevalence of ipsilateral high-risk carotid plaques across seven studies was 28% compared with 4% for contralateral plaques (Figure 2).…”
Section: Carotid Atherosclerosismentioning
confidence: 89%
“…26 In particular, mildly stenotic carotid arteries in patients with ESUS had higher IPH compared with moderate and severe stenosis. 26 The pooled prevalence of ipsilateral high-risk carotid plaques across seven studies was 28% compared with 4% for contralateral plaques (Figure 2).…”
Section: Carotid Atherosclerosismentioning
confidence: 89%
“…109 Intraplaque hemorrhage is another strong indicator of symptomatic plaque and is associated with stroke reoccurrence. 110 Histopathologic studies of extracranial cervical artery specimens have validated intraplaque hemorrhage as plaques with high-signal intensity on T1 weighted images. 111 Unlike in vivo validation of plaque characteristics for carotid atherosclerosis due to sample availability from carotid endarterectomy, in vivo validation for intracranial arteries remains a challenge.…”
Section: Imaging In Icadmentioning
confidence: 99%